Synthesis and Evaluation of Novel Acyclic Nucleoside Phosphonates as Inhibitors of Plasmodium falciparum and Human 6‐Oxopurine Phosphoribosyltransferases. Issue 10 (25th August 2015) - Kaiser, Martin M.; Hocková, Dana; Wang, Tzu‐Hsuan; Dračínský, Martin; Poštová‐Slavětínská, Lenka; Procházková, Eliška; Edstein, Michael D.; Chavchich, Marina; Keough, Dianne T.; Guddat, Luke W.; Janeba, Zlatko
Abstract Acyclic nucleoside phosphonates (ANPs) are a promising class of antimalarial therapeutic drug leads that exhibit a wide variety of Ki values for Plasmodium falciparum (Pf) and human hypoxanthine‐guanine‐(xanthine) phosphoribosyltransferases [HG(X)PRTs]. A novel series of ANPs, analogues of previously reported 2‐(phosphonoethoxy)ethyl (PEE) and (R, S)‐3‐hydroxy‐2‐(phosphonomethoxy)propyl (HPMP) derivatives, were designed and synthesized to evaluate their ability to act as inhibitors of these enzymes and to extend our ongoing antimalarial structure–activity relationship studies. In this series, (S)‐3‐hydroxy‐2‐(phosphonoethoxy)propyl (HPEP), (S)‐2‐(phosphonomethoxy)propanoic acid (CPME), or (S)‐2‐(phosphonoethoxy)propanoic acid (CPEE) are the acyclic moieties. Of this group, (S)‐3‐hydroxy‐2‐(phosphonoethoxy)propylguanine (HPEPG) exhibits the highest potency for PfHGXPRT, with a Ki value of 0.1 μM and a Ki value for human HGPRT of 0.6 μM. The crystal structures of HPEPG and HPEPHx (where Hx=hypoxanthine) in complex with human HGPRT were obtained, showing specific interactions with active site residues. Prodrugs for the HPEP and CPEE analogues were synthesized and tested for in vitro antimalarial activity. The lowest IC50 value (22 μM) in a chloroquine‐resistant strain was observed for the bis‐amidate prodrug of HPEPG.